The Implementation of the Merdeka Curriculum in Phase F History Subjects at SMAN 1 Tumpang - Friska Wulandari; Indah Wahyu Puji Utami (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2026)
This research examines the implementation of the Merdeka Curriculum in Phase F history subjects at SMAN 1 Tumpang, motivated by the co-19 pandemic which exacerbated the education crisis in Indonesia. The purpose of this study is to understand the process, supporting factors, and obstacles faced by teachers and their impact on students. The learning model applied in this school is project-based learning and discovery learning which is centered on students. This research applies a qualitative method, in which researchers try to interpret the data obtained in the field based on the results of observations in class XI and interviews with the Head of Curriculum, history teacher, P5 team coordinator, and students. The results indicated that the implementation of Merdeka Curriculum in Phase F history subjects at SMAN 1 Tumpang was carried out effectively. This is due to supporting factors, namely the availability of adequate learning facilities. The obstacles experienced are the limited effective hours of learning because they are cut with activities outside of learning. The positive impact felt by educators is the ease in terms of delivering material including the depth of material and in terms of assessment, and the enthusiasm for learning of students increases through the use of the project-based learning model.